Temperature-dependent growth and behavior of juvenile Arctic cod (Boreogadus saida) and co-occurring North Pacific gadids - Laurel, Benjamin J.; Spencer, Mara; Iseri, Paul; Copeman, Louise A. (Polar biology, 2016)
The thermal sensitivity of Arctic fish species is poorly understood, yet such data are a critical component of forecasting and understanding ecosystem impacts of climate change. In this study, we experimentally measured temperature-dependent growth and routine swim activity in the juvenile stage of two Arctic gadids (Arctic cod, Boreogadus saida and saffron cod, Eleginus gracilis ) and two North Pacific gadids (walleye pollock, Gadus chalcogrammus and Pacific cod, Gadus macrocephalus ) over a 6-week growth period across five temperatures (0, 5, 9, 16 and 20 °C). Arctic cod demonstrated a cold-water, stenothermic response in that there was relatively high growth at 0 °C (0.73 % day −1 ), near-maximal growth at 5 °C (1.35 % day −1 ) and negative impacts on activity, growth and survival at 16 °C. In contrast, saffron cod demonstrated a warmer-water, eurythermic response, and temperature had a positive effect on growth and condition beyond 16 °C. However, despite these distinct thermal responses, walleye pollock and Pacific cod grew 2–3 times faster than Arctic gadids across a relatively broad temperature range above 5 °C. These results, coupled with possible northward expansion by both Pacific cod and walleye pollock, suggest Arctic cod are highly vulnerable to continued climate change in the Arctic, especially in coastal areas of the Beaufort and Chukchi Seas where temperatures already exceed 14 °C in the summer growth period.